2011
DOI: 10.1007/s12665-011-0913-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial prediction of soil erosion risk by remote sensing, GIS and RUSLE approach: a case study of Siruvani river watershed in Attapady valley, Kerala, India

Abstract: Siruvani watershed with a surface area of 205.54 km 2 (20,554 hectare), forming a part of the Western Ghats in Attapady valley, Kerala, was chosen for testing RUSLE methodology in conjunction with remote sensing and GIS for soil loss prediction and identifying areas with high erosion potential. The RUSLE factors (R, K, LS, C and P) were computed from local rainfall, topographic, soil classification and remote sensing data. This study proved that the integration of soil erosion models with GIS and remote sensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(55 citation statements)
references
References 29 publications
0
55
0
Order By: Relevance
“…Information on factors leading to soil erosion can be utilized as a guide for formulating appropriate soil conservation and land management plans. The Revised Universal Soil Loss Equation (RUSLE) is frequently used to estimate the magnitude of soil erosion loss from watershed areas, the spatial distribution of soil erosion severity, and delimiting sites vulnerable to soil erosion for both agricultural and forested watersheds [30,[42][43][44][45][46][47][48]. Finally, the RUSLE model has several advantages: 1) it is easy to implement and understand from a functional perspective [32], 2) is compatible with the Geographic Information System (GIS), and 3) the data requirements to implement the model are not too complex or unattainable especially in a developing country [49].…”
Section: Soil Loss Estimation Methodsmentioning
confidence: 99%
“…Information on factors leading to soil erosion can be utilized as a guide for formulating appropriate soil conservation and land management plans. The Revised Universal Soil Loss Equation (RUSLE) is frequently used to estimate the magnitude of soil erosion loss from watershed areas, the spatial distribution of soil erosion severity, and delimiting sites vulnerable to soil erosion for both agricultural and forested watersheds [30,[42][43][44][45][46][47][48]. Finally, the RUSLE model has several advantages: 1) it is easy to implement and understand from a functional perspective [32], 2) is compatible with the Geographic Information System (GIS), and 3) the data requirements to implement the model are not too complex or unattainable especially in a developing country [49].…”
Section: Soil Loss Estimation Methodsmentioning
confidence: 99%
“…Spatial and quantitative information on soil erosion on a watershed scale contributes significantly to soil conservation management, erosion control, and catchment environment management [21]. Previous studies showed that assessment of soil erosion methods mainly included empirical models [22,23], physically based models [15,[24][25][26], nuclear tracing [27], and spatially distributed multivariate models [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…This approach has proved to be a successful and inexpensive method for erosion risk assessment (Tian et al 2009;Zhang et al 2010). The quantitative methods are mainly model building (e.g., USLE, RUSLE, CORINE, PESERA and WEPP) (Panagos et al 2014;Prasannakumar et al 2011;Silva et al 2012;Tsara et al 2006). The Universal Soil Loss Equation (USLE) is a commonly used and simple soil erosion model, which estimates long-term average annual soil loss per unit area based on erosion factors (Laflen and Moldenhauer 2003), and the Revised Universal Soil Loss Equation (RUSLE) is a revised method of USLE methodology incorporating additional data (Renard et al 1991).…”
Section: Introductionmentioning
confidence: 99%